Corrosion Behavior of 13Cr Casing Steel in Cement-Synthetic Pore Solution Exposed to High Pressure CO2 and H2S. (9th December 2015) - Feng, Ruishu; Beck, Justin; Hall, Derek M.; Buyuksagis, Aysel; Ziomek-Moroz, Margaret; Lvov, Serguei N.
Abstract : The electrochemical corrosion behavior of grade L-80, type 13Cr casing steel was investigated in cement-synthetic pore solution (CSPS) exposed to CO2 and H2 S using in-situ electrochemical methods and ex-situ surface analyses at 85 and 200 °C, respectively. Total system pressure was 10 MPa. Corrosion rates increased significantly when the temperature increased from 85 to 200 °C. Limiting current behavior was observed for the anode reaction, while charge-transfer control was observed for the cathode reaction. Surface analyses revealed the presence of CaCO3 on the surface at both temperatures and FeCO3 -like deposits at 200 °C.